Effects of High-Intensity Strength Training in Adults With Knee Osteoarthritis: A Systematic Review and Meta-analysis of Randomized Controlled Trials - Hua, Jiong; Sun, Lin; Teng, Yue (American journal of physical medicine & rehabilitation, 2023)
The aim of the study is to assess the effects of high-intensity strength training versus low-intensity strength training or routine care in adults with knee osteoarthritis. PubMed, Embase, Cochrane Library, and Web of Science were searched up to March 10, 2021. The outcomes were knee pain, knee function, quality of life, and adverse events. Ten studies of 892 subjects with knee osteoarthritis were included. No significant differences were found between the high-intensity strength training group and the low-intensity strength training or routine care group in the Western Ontario and McMaster Universities Osteoarthritis Index pain score, Knee Injury and Osteoarthritis Outcome Score pain score, Western Ontario and McMaster Universities Osteoarthritis Index stiffness score, Western Ontario and McMaster Universities Osteoarthritis Index physical function score, Knee Injury and Osteoarthritis Outcome Score symptom score, Knee Injury and Osteoarthritis Outcome Score activities of daily living score, Knee Injury and Osteoarthritis Outcome Score sport and recreation score, Timed Up and Go result, gait velocity, walking time, peak torque of the knee extensors, Knee Injury and Osteoarthritis Outcome Score quality of life score, and adverse event incidence (all P > 0.05). The peak torque of the knee flexors at 120-degree per sec contraction (pooled weighted mean difference, 7.520; 95% confidence interval, 1.256 to 13.784; P = 0.019) in the high-intensity group was improved significantly than that in the low-intensity training or routine care group. High-intensity strength training may have similar effects in improving knee pain, knee function, and quality of life, with comparable safety to low-intensity strength training and routine care.